Pulmonary Rehabilitation and Asthma - Zampogna, Elisabetta; Zappa, Martina; Spanevello, Antonio; Visca, Dina (Frontiers in Pharmacology, 2020)
Asthma is a chronic inflammatory disease characterized by airflow limitation and variable respiratory symptoms. It is characterized by variable symptoms such as cough, wheeze, chest tightness and shortness of breath which vary in intensity and time. In order to reach a comprehensive approach of disease management, the importance of non-pharmacological treatment in addition to pharmacological therapy has been recently highlighted. Studies have documented that pulmonary rehabilitation has beneficial effects in patients with asthma, at any stage of the disease, improving exercise capacity, asthma control and quality of life and reducing wheezing, anxiety, depression and bronchial inflammation. Although several evidences suggest a role of pulmonary rehabilitation in patients with asthma, additional information is required to identify a specific program in order to improve clinical care based on specific patient’s needs.